Ethics with Barth : God, Metaphysics and Morals. (Ashgate Gower, 2010)
Matthew Rose offers the first treatment of Barth's ethics from a Roman Catholic perspective, focusing particularly on Barth's "ethics of creation" in Church Dogmatics III/4. Among the topics treated are: the connection between dogmatics and ethics, the trinitarian nature of Christian ethics, the relation between theological ethics and Christian moral philosophy, the nature of the divine good, Barth's conception of moral reasoning, and his views on eudaimonism and the natural law.
Cover -- Contents -- IntroductionChristian by Nature? -- Part 1 -- 1 The Humanity of God -- 2 What There Is -- 3 The Measure of All Things -- Part 2 -- 4 The Sovereign Good -- 5 The Will to Joy -- 6 The Imperative of Reality -- 7 A Christian Sociology -- 8 Humanity Against Itself -- EpilogueBarthian Difficulties -- Bibliography -- Index.
Master record variable field(s) change: 072
Keywords: Barth, Karl, -- 1886-1968.; Barth, Karl, -- 1886-1968.; Christian ethics -- Reformed authors; RELIGION / Christian Theology / Ethics; Electronic resource; Electronic books